Controlled release of drugs from cellulose acetate matrices produced from sugarcane bagasse: monitoring by square-wave voltammetry - Rodrigues Filho, Guimes; Almeida, Flavia; Ribeiro, Sabrina D.; Tormin, Thiago F.; Munoz, Rodrigo A. A.; Assuncao, Rosana M. N.; Barud, Hernane [UNESP] (Taylor & Francis Ltd, 2016)
In this paper, cellulose triacetate (CTA) was produced from sugarcane bagasse and used as matrices for controlled release of paracetamol. Symmetric and asymmetric membranes were obtained by formulations of CTA/dichloromethane/drug and CTA/dichloromethane/water/drug, respectively, and they were characterized by scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). Different morphologies of membranes were observed by SEM, and the incorporation of paracetamol was confirmed by lowering of the glass transition temperature (T-g) in the DSC curves. This indicates the existence of interactions between the matrix and the drug. The evaluation of drug release was based on the electrochemical monitoring of paracetamol through its oxidation at a glassy carbon electrode surface using square-wave voltammetry (SWV), which provides fast, precise and accurate in situ measurements. The studies showed a content release of 27% and 45% by the symmetric and asymmetric membranes, respectively, during 8h.
Keywords: Cellulose acetate; controlled release; membranes; square wave voltammetry; sugarcane bagasse